Cardiovascular Events in Systemic Lupus Erythematosus: A Nationwide Study in Spain From the RELESSER Registry - Fernández-Nebro, Antonio (Medicine (Baltimore), 2015)
This article estimates the frequency of cardiovascular (CV) events that occurred after diagnosis in a large Spanish cohort of patients with systemic lupus erythematosus (SLE) and investigates the main risk factors for atherosclerosis. RELESSER is a nationwide multicenter, hospital-based registry of SLE patients. This is a cross-sectional study. Demographic and clinical variables, the presence of traditional risk factors, and CV events were collected. A CV event was defined as a myocardial infarction, angina, stroke, and/or peripheral artery disease. Multiple logistic regression analysis was performed to investigate the possible risk factors for atherosclerosis. From 2011 to 2012, 3658 SLE patients were enrolled. Of these, 374 (10.9%) patients suffered at least a CV event. In 269 (7.4%) patients, the CV events occurred after SLE diagnosis (86.2% women, median [interquartile range] age 54.9 years [43.2–66.1], and SLE duration of 212.0 months [120.8–289.0]). Strokes (5.7%) were the most frequent CV event, followed by ischemic heart disease (3.8%) and peripheral artery disease (2.2%). Multivariate analysis identified age (odds ratio [95% confidence interval], 1.03 [1.02–1.04]), hypertension (1.71 [1.20–2.44]), smoking (1.48 [1.06–2.07]), diabetes (2.2 [1.32–3.74]), dyslipidemia (2.18 [1.54–3.09]), neurolupus (2.42 [1.56–3.75]), valvulopathy (2.44 [1.34–4.26]), serositis (1.54 [1.09–2.18]), antiphospholipid antibodies (1.57 [1.13–2.17]), low complement (1.81 [1.12–2.93]), and azathioprine (1.47 [1.04–2.07]) as risk factors for CV events. We have confirmed that SLE patients suffer a high prevalence of premature CV disease. Both traditional and nontraditional risk factors contribute to this higher prevalence. Although it needs to be verified with future studies, our study also shows—for the first time—an association between diabetes and CV events in SLE patients.